POTENSI BAHAN ALAM UNTUK DIABETES MELLITUS DI WILAYAH RW 03 KELURAHAN KLENDER JAKARTA TIMUR - Pra Panca Bayu Chandra; Pricillya Maria Loimalitna; Rohima Robby (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Hyperglycemia is a medical condition characterized by elevated blood glucose levels above normal, often associated with diseases such as Diabetes Mellitus (DM). According to data from the Indonesian health Survey in 2023, the prevalence of DM based on doctor's diagnoses in the population of all ages in DKI Jakarta Province ranked 4th. Using natural ingredients to help regulate blood glucose levels is a cost-effective and minimally side-effect approach, as these raw materials are readily available. The aim of the Community Service (PkM) activity in the RW 03 area of Klender Village, East Jakarta, was to educate the public on the use of natural ingredients for blood glucose control. The PkM activity was attended by 18 residents from RW 03 in Klender Village and the results showed a 22% increase in respondents' knowledge about natural ingredients for blood glucose control.